2009
DOI: 10.1152/ajprenal.90566.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytosolic NADP+-dependent isocitrate dehydrogenase in ischemia-reperfusion injury in mouse kidney

Abstract: Cytosolic NADP+-dependent isocitrate dehydrogenase (IDPc) synthesizes reduced NADP (NADPH), which is an essential cofactor for the generation of reduced glutathione (GSH), the most abundant and important antioxidant in mammalian cells. We investigated the role of IDPc in kidney ischemia-reperfusion (I/R) in mice. The activity and expression of IDPc were highest in the cortex, modest in the outer medulla, and lowest in the inner medulla. NADPH levels were greatest in the cortex. IDPc expression in the S1 and S2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…Western blot analyses were conducted as previously described (20,22,34). In brief, renal tissue or cell lysates (30 -50 g protein/lane) were separated on 10 or 12% SDS-PAGE gels and then transferred to Immobilon membranes (Millipore, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analyses were conducted as previously described (20,22,34). In brief, renal tissue or cell lysates (30 -50 g protein/lane) were separated on 10 or 12% SDS-PAGE gels and then transferred to Immobilon membranes (Millipore, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
“…This excessive ROS generation induces lipid peroxidation, inactivation of antioxidant enzymes, disruptions of the cellular cytoskeleton, cellular integrity, DNA breakdown, leukocyte activation, endothelial cell damage, and cytokine production, all factors which contribute to tissue damage (3,8,21,32). Antioxidant agents have been used to prevent tissue damage in various clinical settings and experimental models (20,41,51). We previously demonstrated that a treatment of manganese(III) tetrakis(1-methyl-4-pyridyl) porphyrin [MnTMPyP; a cell-permeable superoxide dismutase (SOD) mimetic] prevented the postischemic increases in lipid peroxidation and hydrogen peroxide levels, resulting in reduced kidney injury from I/R in mice (18).…”
mentioning
confidence: 99%
“…Immunofluorescent staining was performed as we previously described (18,21,23). Briefly, to reveal antigen epitope, the sections were boiled in 10 mM sodium citrate buffer (pH 6.0).…”
mentioning
confidence: 99%
“…Ischemia causes ATP depletion, which induces necrotic and apoptotic cell death. Following reperfusion, cell damage is worsened to an extent greater than ischemia itself, due to the production of excessive ROS including superoxide anions, hydroxyl radicals, hypochlorous acid, hydrogen peroxide, and peroxynitrite (15,34,42). The ROS levels are excessively increased beyond the antioxidant capacity of the cells.…”
mentioning
confidence: 99%